Variantes do gene NOTCH1 como biomarcadores para transtornos neurocognitivos - Rodrigues, Alda dos Santos (2025)
Neurocognitive disorder (NCD) can be mild (TNCL) when it does not impact independence in activities of daily living or major (TNCM), also known as dementia, is clinically heterogeneous and has been associated with different risk factors, such as metabolic diseases (diabetes, obesity), stroke, tobacco and alcohol use, among others. Genetic factors have been investigated, but are not yet fully known. Thus, the search for biomarkers that can be used in diagnosis, risk screening, prognosis and response to treatment is very important. In this context, the NOTCH1 gene is expressed in several tissues, mainly in the cerebral cortex, hippocampus and cerebellum, hematopoietic stem cells, heart and blood vessels, and is associated with 118 phenotypes. NOTCH1 encodes a protein homologous to the neurogenic NOTCH locus in humans (Homo sapiens), important for glucose homeostasis, lipid metabolism, cell growth and survival. The NOTCH signaling pathway is very important in neurogenesis and maintenance of adequate neuronal function in the human brain and has been implicated in NCD//dementia, including Alzheimer's disease (AD). Recent evidence points to a shared genetic architecture between metabolic alterations, NOTCH1 and NCD. NOTCH1 is expressed in the mature human hippocampus, and shows increased immunoreactivity in AD, and in cases with tau-positive Pick bodies. The absence of NOTCH1 is capable of affecting a cascade of secondary messengers associated with plasticity and spatial learning, and with reduced volume of brain regions, being associated with AD and, therefore, with the risk of NCD. Thus, the hypothesis tested in this work is that variants in this gene are associated with NCD. The objective is to verify whether variants in NOTCH1 are associated with NCD. Participants in the PAHO study "Health, Well-being and Aging" (SABE) from São Paulo, with complete data (N=1103), were classified for NCD using the score obtained in the Mini Mental State Examination (MMSE). Participants who scored below the MMSE cutoff (13 points) were considered cases [carriers of NCD (N=152)] and the remaining participants (951), with a score of 13 or higher, were used as controls. Clinical data were obtained from a standardized questionnaire and genetic data from whole-genome sequencing to identify genetic variants. Genotypes for the variants and their respective frequencies were obtained from the Brazilian Online Mutation Archive (ABraOM). Females comprised the majority of the population, corresponding to 64.09% (N=707). The prevalence of NCD was 13.78% (152 patients). The variants rs10870087, rs2990585, rs7874114 and rs7864342 associated with NCD were identified in DNA regulatory regions, mainly in active enhancers, suggesting their role in the regulation of gene expression, especially in brain tissues. The rs2990585 and rs7874114 variants have epigenetic marks (H3K27ac and H3K4me1), indicating involvement in the activation of genes related to synaptic plasticity and neurodevelopment. rs2990585 with a high probability of regulatory function (1f), binding to the CEBPA gene, involved in cell differentiation and inflammatory response. Enhancer 2 of this variant is active in several brain regions, such as the midbrain and frontal cortex. Furthermore, the rs10870087, rs7864342 and rs7874114 variants demonstrated eQTL activity for CYSRT1 in breast tissue, while rs2990585 presented eQTLs in genes such as NOTCH1 (blood and tibial artery) and NRARP (lymphocytes). These findings suggest that variants in NOTCH1 have an impact on gene regulation and are promising candidates for use as biomarkers of NCD. However, functional studies and studies in other populations are needed for generalization and application of these results